Considerations about Heart Diseases of Rheumatic Diseases - Andrade, Pedro Ikaro Rodrigues de (2023)
Several autoimmune rheumatic diseases (ARD) are responsible for the increased risk of cardiovascular comorbidities, whether due to atherosclerosis, thrombus formation, vasculitis or myocardial inflammation. The improvement of therapeutic practices and the increase in life expectancy of patients brought a new look at cardiovascular complications resulting from rheumatological disorders. This article considers heart disease in Rheumatic Diseases. The results demonstrated that physical activity is one of the most important behavioral interventions, as a beneficial impact on the probability of developing, suffering symptomatically or dying from CVD. Thus, maintaining a healthy lifestyle reduces risk factors for CVD, including obesity, dyslipidemia, hypertension, diabetes mellitus and possibly even inflammation. It also showed efficacy in preventing acute coronary syndromes. Exercise seems to help manage established CVDs, be it aerobic exercise or resistance training. They improve myocardial contractility and quality of life in patients with chronic heart failure.